Photoprotective Effect of the Plant Collaea argentina against Adverse Effects Induced by Photodynamic Therapy - Leandro Mamone; Daniel Sáenz; Pablo Vallecorsa; Alcira Batlle; Adriana Casas; Gabriela Di Venosa (International Journal of Photoenergy)
Photodynamic therapy (PDT) is a treatment modality for tumours and other accessible lesions based on the combination of light and a photosensitizer (PS) accumulated in the target tissue. The main disadvantage of PDT is PS retention after treatment during long time periods that conduces to cutaneous damage. It is believed that singlet oxygen is responsible for that skin photosensitization. The aim of this work was to evaluate the photoprotective activity of the methanolic extract of the Argentinian plant Collaea argentina against PDT under several treatments and employing different PSs. C. argentina exhibited photoprotective activity against aminolevulinic acid- (ALA-) PDT in the LM2 murine adenocarcinoma cell line. The photoprotection was dependant on the extract concentration and the incubation time, being detectable from 40 μg/mL onwards and at least after 3 h exposure of the cells. C. argentina extract protects these mammalian tumor cells against PDT effects, and it interferes with the oxygen singlet production from PSs during PDT treatment. We propose that it will be a promising agent to protect cells against PDT-induced skin sensitivity.